Management and services of muslim cemetry inklang valley area / Nur Afiqah Nadhirah Khair Siddik, Aimie Diyanna Mohd Rosli … [et al.] - KHAIR SIDDIK, NUR AFIQAH NADHIRAH; MOHD ROSLI, AIMIE DIYANNA; GHAZALI, INTAN IZZATI; MOHD SHAFRIDIN, MOHD SHAMIRUL (2019)
Jannatul Akhirah Sdn Bhd exist to help in managed an industry and provide services to the industry that other business would not even think to get involved with which is managing Muslim Cemetry in Klang Valley area and provide services on handling the procedure of deceased burial.We come acrossed this business opportunity when there's too many abandoned Muslim Cemetry without proper management and maintenance. We have done some survey about the importance of the Mulsim Cemetry that focusing towards deceased closed family or relatives in how they would to preserved the deceased graveyard. Turn out that most of the deceased closed family or relatives concerned about the maintenance of the deceased graveyard but due to time-constraints and other commitment make them hardly to taking care the graveyard. Based on these opportunity, we, Jannatul Akhirah Sdn Bhd, come out with these services that focusing on managing the Muslim Cemetry and at the same time providing services in helping the deceased closed family to execute the burial procedure